NECROTIC ENTEROCOLITIS OF NEWBORNS (literature review) - Chartakov, Dilmurod (Medical science of Uzbekistan, 2025)
Necrotizing enterocolitis (NEC) is a neonatal inflammatory bowel disease and is one of the most threatening disease in neonatal gastroenterology. The average incidence of necrotizing enterocolitis 2,4:1000 infants (1 to 10:1000), or about 2.1% (from 1 to 7%) of the total number of children entering the neonatal intensive care unit. The incidence of disease increases with decreasing gestational age at birth. The share of full-term infants accounts for 10-20% of cases of NEC. In recent years, necrotic enterocolitis has remained one of the leading causes of morbidity and mortality among premature infants with low body weight. The active study of the most important diagnostic factors in the early stages of the disease, which is difficult to diagnose, the choice of a treatment method is one of the first tasks of neonatologists and surgeons of the children's department.